2020
DOI: 10.1093/advances/nmaa051
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Chrono-nutrition and Cardiometabolic Health: A Narrative Review of the Evidence

Abstract: Growing evidence suggests that personality traits play a role in obesity and cardiometabolic health. In addition, irregularity of food intake has emerged as a potential risk factor for obesity, cardiovascular disease, and metabolic syndrome. Recent studies suggest that when we eat, termed “chrono-nutrition,” may be as important to what we eat. This concept covers 3 aspects: 1) irregularity of energy intake in meals (varying amounts of energy intake throughout the day and at different times from one day to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
0
19
1
1
Order By: Relevance
“…Future research with longitudinal designs which studies changes in BPI after treatments, and analyzes correlations between BPI, quality of life, and pain in time, are needed. On the other hand, research into other factors that can influence BPI (mainly those related to neurohumoral, immunological, and autonomic nervous factors and therefore cell metabolism), such us dietary habits and exercise are required [ 49 , 50 , 51 , 52 ]. Furthermore, building and researching biopsychosocial clinical approaches which include variations in circadian BP would strengthen and benefit the understanding and treatment of CMP.…”
Section: Discussionmentioning
confidence: 99%
“…Future research with longitudinal designs which studies changes in BPI after treatments, and analyzes correlations between BPI, quality of life, and pain in time, are needed. On the other hand, research into other factors that can influence BPI (mainly those related to neurohumoral, immunological, and autonomic nervous factors and therefore cell metabolism), such us dietary habits and exercise are required [ 49 , 50 , 51 , 52 ]. Furthermore, building and researching biopsychosocial clinical approaches which include variations in circadian BP would strengthen and benefit the understanding and treatment of CMP.…”
Section: Discussionmentioning
confidence: 99%
“…Chrono-nutrition is a new nutritional research field, which aims to explore whether and how the intake time of diet would affect health ( 1 ). Accumulating studies have demonstrated that diet intake time is important for wellbeing, independent of the quality and quantity of a diet ( 2 , 3 ). Currently, most of the studies have mainly focused on the intake time of energy and macronutrients and have demonstrated that consuming them at different time periods influenced the oscillation of the circadian clock genes, resulting in different health effects ( 4 , 5 ); however, few studies have examined whether and how the micronutrient intake time would impact health.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews identified a link between obesity and individual biological rhythm and feeding time. Inconsistent and irregular timing of food intake is associated with increased body weight [ 5 ]. Chronobiological studies investigating the rhythmic change of vital phenomena over time are clarifying the metabolic and circadian background of obesity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%